Steady-state Coupling of Plasma Membrane Calcium Entry to Extrusion Revealed by Novel L-type Calcium Channel Block - Lester, William C (2008)
The L-type Ca(2+) channel (Ca(V)1.2) is the main pathway for trans-sarcolemmal (SL) Ca(2+) influx in cardiac myocytes. To maintain Ca(2+) homeostasis, chronic SL Ca(2+)-influx must be matched by chronic SL efflux. In this study we tested the hypothesis that chronic down-regulation of SL Ca(2+)-entry regulates SL extrusion. We studied mRNA and Ca(2+) handling responses to chronic down-regulation of Ca(2+) channel current induced by over-expression of the small GTPase Rem. Rem lowered net SL diastolic Ca(2+)-entry, and reduced the twitch Ca(2+) amplitude. Rem also significantly slowed Ca(2+) transient decay kinetics (p<10(-3)). Rem reduced NCX1.1 protein level and function. To measure Na-Ca(2+)-exchange (NCX) function and sarcoplasmic reticulum (SR) store load we perfused Ca(2+)-free bath for 25s followed by rapid application of 50mM caffeine. In control, caffeine transient relaxations were described by a bi-exponential decay with a fast phase that was 10mM Ni(2+)-senstive. Rem significantly slowed caffeine-induced relaxation time course (Rem vs control, p<10(-6)). To test whether extrusion slowing was mediated by insufficient basal Ca(2+) for allosteric NCX activation we measured the effect of increasing bath Ca(2+) from 1.8 to 6mM on caffeine-induced relaxation kinetics. 6mM Ca(2+) did not alter kinetics of control cells, but in Rem-over-expressed cells 6mM Ca(2+) sped kinetics. We conclude that chronic block of Ca(V)1.2 channel-mediated SL entry alters NCX expression, and coincidentally controls SR Ca loading and SL Ca(2+) efflux.